Optimalisasi Peningkatan Produktivitas Lahan Kering Melalui Penanaman Tumpangsari Jagung - Kacang Tanah Di Desa Mbawi Kabupaten Dompu - A. Farid Hemon; I Gusti Putu Muliartha Aryana; I Wayan Sutresna; Kisman Kisman (Unram Journal of Community Service, 2023)
The purpose of this activity is to increase the knowledge and skills of farmer groups to understand increasing the productivity of dry land by implementing corn-peanut intercropping cultivation. The program that has been implemented is the application of science and technology, with the stages of activities, namely: 1) dissemination activities on optimizing dry land with the corn-peanut overlapping technique, selecting peanut corn varieties that are adaptive to dry land and shade, as well as plant cultivation techniques on land dry. This activity was carried out with a system of lectures and discussions between the Extension Team and the Farmers' Group, and 2) a demonstration plot program involving farmers from the preparation/planning of the program to the implementation of the demonstration plots. Farmers directly participate in planting, maintaining, comparing, and evaluating whether the implemented program will provide benefits or not. The results of the activity showed that the farmers participating in the extension were very responsive to the corn-peanut intercropping dissemination activity. This is reflected in the enthusiasm of the participants in asking questions and the discussions between the participants or extension workers. In addition, participants were also active in participating in every stage of activities such as selecting good seeds, making demonstration plots, planting, stockpiling, weeding, pest and disease control, and harvesting activities. There is a process of technological transformation of corn-peanut intercropping on the dry land of Mbawi Village, Dompu District, Dompu Regency, with the hope that farmers will be able to utilize the dry land by intercropping. Intercropping can increase land productivity with a Land Equivalent Ratio (LER) value of 1.3 compared to corn monoculture and 3.1 compared to peanut monoculture